2003
DOI: 10.1213/01.ane.0000054003.03645.cf
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Analgesic Doses of Fentanyl and Sufentanil for Epidural Analgesia in the First Stage of Labor

Abstract: This study determined the minimum analgesic doses of fentanyl and sufentanil for epidural anesthesia in the first stage of labor. The sufentanil/fentanyl potency ratio was 5.9. This ratio may be used to establish the equivalent doses for fentanyl and sufentanil for epidural analgesia in labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
4
29
1
Order By: Relevance
“…Both doses were decided according to the median effective dose (ED50) of sufentanil for intrathecal and epidural adminis tration as published by Herman et al [12] and Capogna et al [6], respectively. At the reappearance of pain (Numeric Rating Scale (NRS) >4), analgesia was continued in both groups with the same protocol of epidural boluses of levobupivacaine + sufentanil according to cervical dilatation and conforming to our Institutional Protocol (Table 2).…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both doses were decided according to the median effective dose (ED50) of sufentanil for intrathecal and epidural adminis tration as published by Herman et al [12] and Capogna et al [6], respectively. At the reappearance of pain (Numeric Rating Scale (NRS) >4), analgesia was continued in both groups with the same protocol of epidural boluses of levobupivacaine + sufentanil according to cervical dilatation and conforming to our Institutional Protocol (Table 2).…”
Section: Interventionmentioning
confidence: 99%
“…The administration of perimedullary opioids in combination with lower concentration of local anesthetic has been gaining popularity to maintain some degree of motor function during the labor [1,3,4] and reduce local anesthetic requirements [5]. In this regard, Sufentanil has emerged as one of the most useful drugs for pain relief due to its potency (5-6 times that of fentanyl) [6], longer analgesic effect [7] and relatively safe profile. However, opioids have also been associated with dose-related side effects such as pruritus, respiratory depression and maternal hypotension [8].…”
Section: Introductionmentioning
confidence: 99%
“…10 The potency ratio of epidural sufentanil:fentanyl was reported as 5:1 by Herman et al and 5.9:1 by Capogna et al, and they observed less side effects like somnolence and pruritus with sufentanil compared to fentanyl. 6,7 Sufentanil is preferred for epidural administration because of its high lipid solubility and high affinity for mu opioid receptors. It penetrates to spinal cord rapidly, leaving cerebrospinal fluid and this prevents the delayed respiratory depression.…”
Section: Group 1 Group 2 Pmentioning
confidence: 99%
“…Sufentanil is the most potent opioid. [2][3][4][5][6][7] Bupivacaine and sufentanil are frequently used together. 1,[8][9][10] However, the lowest doses that produce effective analgesia is still controversial.…”
mentioning
confidence: 99%
“…Capogna et al determined the ED50 of epidural fentanyl and sufentanil using the MLAC methodology (194). To produce analgesia in 50% of patients a dose of 124 µg fentanyl and 21 µg sufentanil was required, establishing a potency ratio of 5.9 between sufentanil and fentanyl.…”
Section: Opioidsmentioning
confidence: 99%